(untitled) (Ekonomski vjesnik/Econviews - Review of Contemporary Business, Entrepreneurship and Economic Issues, 2018)
Small grocery stores are forced to look for ways to retain customers. One possibility is through collaboration with suppliers. Therefore, the aim of this research was to determine the forms of collaboration between small Czech grocery stores and suppliers and to specify the differences in this collaboration depending on store location and the possible affiliation of the store with a retail chain. To achieve this goal, quantitative research was carried out among 65 Czech retail stores using face-to-face interviews with predetermined questions. Collaboration was assessed on the basis of four criteria defined by the authors. It was found that the most frequently occurring element of collaboration was the provision of trade credit to retailers – less often, long-term contracts and synchronization of replenishment. The least used was information sharing. The research results show that the form of collaboration is significantly affected by customer value. Therefore, the level of collaboration can be improved by building horizontally interconnected retail chains. The paper enriches theoretical knowledge by specifying possible elements of collaboration between small retail stores and suppliers and mapping the frequency of their implementation. Keywords: Customer value; replenishment; retail management; retail store; supply chain collaboration